Enhancing E-Commerce Readiness of Regional Flagship Product: AHP-Based Packaging Selection for Kembang Goyang - Perak Samosir; Yenny Widianty; Ratnawati Ratnawati; Ruth Nattassha (Community Engagement and Emergence Journal (CEEJ), 2026)
This study aims to determine the most appropriate packaging for kembang goyang to improve the e-commerce readiness of regional flagship product In South Tangerang. This study uses a quantitative method with the Analytical Hierarchy Process (AHP) approach. The study population consists of experts who have experience in food product development and MSME management. The research sample was determined using a purposive sampling technique with 15 experts, consisting of researchers, food experts, and kembang goyang MSME actors. Data were collected through paired comparison questionnaires and analyzed using Expert Choice software. The results show that product protection criteria and packaging strength are the most important factors in packaging selection. Canister packaging becomes the best alternative compared to other packaging. The implications of this study indicate that selecting the right packaging can improve the e-commerce readiness of MSMEs.